Desarrollo e implementación del Sistema de Firmas Electrónicas y Certificados Digitales del Estado e implantación de la autoridad administrativa competente - Vermejo Ruiz, Carlos Rubén Bernardino (2020)
The present work consists of providing and implementing the official infrastructure of the National System of Electronic Signature and Digital Certificates to carry out reliable electronic transactions and thereby contribute to the modernization and decentralization of the State. The Competent Administrative Authority that is the governing body of the National System of Electronic Signature and Digital Certificates will be in charge of approving the national standards and norms of the system; It will start its operation at INDECOPI, in addition, an authority will be implemented to issue and register Digital Certificates for the government at Reniec, and then according to the needs of the State, other public institutions will participate in the system, either as Certification Entities or Registration or Verification Entities. The scope of the project is basically to the public sector, although with the implementation of the governing body, the Competent Administrative Authority, Issuing and Registration Entities of the private sector will be created, which will issue digital certificates that will have legal effect when generated within the official infrastructure of digital signature.